Peran Kapital Sosial dan Kapital Digital pada Produksi dan Pemasaran Urban Farming dalam Peningkatan Pendapatan Petani Urban Miskin Di Banjir Kanal Timur Kelurahan Pondok Kopi Jakarta Timur - Keiko Karina Ueno (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Income is one of the indicators of people's welfare, this also applies to urban farmers. Urban farmers are people who work to maintain plants for their benefits to generate income in urban or urban areas. In previous studies, social capital was considered to be effective in increasing production and marketing, which of course had an impact on farmers' income levels. Likewise with technology, it is undeniable that technology has an important role in the sustainability of activities. This article aims to analyze the existence of the role of social capital and digital capital, as well as the obstacles faced by urban farmers in the East Flood Canal, Pondok Kopi sub-district in developing social capital and digital capital, especially in the production and marketing of urban farming to increase the income of urban farmers in BKT by qualitative descriptive approach. Interviews were conducted with 10 informants using a tap recorder, a notebook to write research findings and documentation in the form of photos while at the research location. The selection of informants was carried out by purposive sampling. The results showed that Social Capital is very important in launching production and marketing activities. Trust, networks, values and norms which are elements of social capital are important elements among urban farmers. The form of trust among urban farmers is by lending each other equipment such as hoes and sickles. A social network between farmers and sellers of fertilizers and seeds in the Cakung market who need each other. Values and norms for each farmer not to interfere with each other's land so as to create smoothness in producing agricultural products. Meanwhile, in operating technological devices, in this case, HP as an element of Digital Capital is very minimal. There are still few urban farmers who use Handphones for marketing activities because they cannot read and write, so farmers find it difficult. However, there are some farmers who already use handphones and find it helpful because they can easily get farming tools at the online shop and get more income compared to farmers who do not use handphones in their marketing.